GE_GERICHTE C/28143/2009 vom 25. Mai 2012 - GE Cour de justice (2012)
BAIL À LOYER ; FRAIS ACCESSOIRES ; MAJORATION DE LOYER ; | CPC.317; CPC.92.2; CO.257a.2; CO.269d.1; OBLF.19.lbis; OBLF.19.1.b; CC.8